2010
DOI: 10.1021/jp911873j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced p-Type Conductivity of ZnTe Nanoribbons by Nitrogen Doping

Abstract: Single-crystalline intrinsic and N-doped p-type ZnTe nanoribbons (NRs) were synthesized via the thermal evaporation method in argon-mixed hydrogen and nitrogen-mixed ammonia, respectively. Both intrinsic and doped ZnTe nanoribbons had zinc blende structure and uniform geometry. X-ray diffraction peaks of N-doped ZnTe nanoribbons had an obvious shift toward higher angle direction as compared with intrinsic ZnTe. X-ray photoelectron spectroscopy detection confirmed that the dopant content of nitrogen in ZnTe nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
(91 reference statements)
6
50
0
Order By: Relevance
“…4c) taken from the branch area B confirmed that the branch was crystallized well. The interplanar distance along the elongation axis of the branch was determined to be 0.31 nm, which was close to the (2 2 0) interplanar distance of cubic ZnTe [27]. Therefore, the crystal growth of the branch was preferential in the (2 2 0) direction.…”
Section: Morphologic and Structural Characterizationsupporting
confidence: 51%
“…4c) taken from the branch area B confirmed that the branch was crystallized well. The interplanar distance along the elongation axis of the branch was determined to be 0.31 nm, which was close to the (2 2 0) interplanar distance of cubic ZnTe [27]. Therefore, the crystal growth of the branch was preferential in the (2 2 0) direction.…”
Section: Morphologic and Structural Characterizationsupporting
confidence: 51%
“…In spite of these progresses, the efficient synthesis of p-type ZnSe nanostructures with reliable and reproducible is much demanded to promote the applications of ZnSe nanostructures in further study. Moreover, N-doping nanostructures such as ZnO NWs and ZnTe NWs via ammonia atmosphere have been reported [27,28]. A simple method with high-doping efficiency is much desired to realize ZnSe nanostructures with well-controlled p-type conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Huo et al [28] have fabricated copper doped zinc telluride (ZnCuTe) nanowires via vapour phase transport method. Li et al [29] have synthesized copper doped zinc telluride (ZnCuTe) nanoribbons via thermal evaporation method. To the best of our knowledge, there is no report on synthesis of ZnCuTe nanowires via template-assisted electrodeposition of so far.…”
Section: Introductionmentioning
confidence: 99%